Domestic Pigeons As A Potential Hazzard For Transmission Of Some Human Protozoan Parasites - Refaat, M.A. Khalifa; Abdallah, A.E. Hassan; Mohsen, I. Arafa; Hanan, E. M. Eldeek; Wafaa, G. Mahmoud (Journal of Parasite Research, 2020)
Domestic pigeons (Columba liviadomestica) of the order Columbiformes are ubiquitous birds and can be found in virtually every town and city around the globe. Their interaction with humans and domestic animals and wild birds makes them a potential carrier of zoonotic parasites. The present study aimed to detect the prevalence of different zoonotic protozoans that affect different-aged domestic pigeons in different localities in Assiut Governorate, Egypt. A total of 50 fecal samples from 20 young and 30 adult pigeons were collected and examined for identification and estimation of prevalence of Cryptosporidium sp. and Microsporidium sp. using modified Kinyoun acid-fast stain. For detection of the prevalence of Toxoplasma gondii, serum samples from 50 pigeons were examined serologically for the presence of Toxoplasma antibodies by using Latex Agglutination test. The prevalence of Cryptosporidium sp. infection was 20%; 6.7% in adult pigeons and 40 % in young pigeons while that of Microsporidium sp. was 40% both in adult and young pigeons. Mixed infection was detected in only two young pigeons (10%). Regarding Toxoplasma gondii detection, the number of seropositive cases detected by LAT was 29 out of 50 (58%). The positive agglutination titers, among 14 (48.27%) seropositive pigeons ranged between 1:2 -1:128. It was concluded that domestic pigeons may be considered as a reservoir host for Cryptosporidium, Microsporidium, and Toxoplasmagondii human infection which represents a serious human public health problem especially for high risk groups of population living in the same dwellings with pigeons. Moreover, the present pilot results provide a baseline data for planning future researches and control strategies against domestic pigeon's parasites.
Keywords: Domestic pigeons; zoonotic parasites; Cryptosporidium; Microsporidium; Toxoplasmagondii